Fish Abundance and Species Composition between Fished and Non-fished Areas of Lake Chivero, Zimbabwe - Muzvondiwa, John V; Chiwara, Joseph; Ngwenya, Mary M (World Wide Journals, 2022)
The main objectives of this study was to compare fish abundance, species composition and fish mean lengths between fished and non-fished (protected) area of Lake Chivero, Zimbabwe. Biological data (species, weight and length) for individual fish sample collected from fished and non fished areas using gillnets of different mesh sizes were recorded. Mean Catch per Unit Effort (CPUE), Species diversity (H'), species richness (S), species evenness and mean fish lengths were determined for each area. A total of eleven fish species from five fish families were caught during the entire study period. The findings revealed that there were significant differences in fish abundance between fished and non-fished areas (P< 0.005) and a non-significant difference in fish species composition and fish mean lengths between the two areas (P> 0.005). This suggests almost equal levels of resources exploitation and disturbances within the two areas or high levels of fish migration from protected areas to re-colonize depleted stocks in fished areas.